The Relationship of Perceived Stigma Among PLHIV with Utilization of Care Support and Treatment (CST) Services in Solo Plus Peer Support Group - Kusumaningrum, Tanjung Anitasari Indah; Larasati, Dwi Intan (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Care, support and treatment (CST) services are among the services needed by PLHIV. This service can improve the quality of life of PLHIV, but there are still PLHIV who do not use the service regularly. The aim of this research is to analyze the relationship between perceived stigma and utilization of CST services. Method: This type of research was quantitative, namely analytical observational (cross sectional). This research was conducted at the Solo Plus Surakarta Peer Support Group with a total sample of 110 PLHIV taken using exhaustive sampling technique. The independent variable was perceived stigma and the dependent variable is utilization of CST services. The instrument for measuring perceptions of stigma used the Berger HIV Stigma Scale while utilization of CST services was measured using a questionnaire that looks at behavior in the last six months. Data analysis was carried out using Fisher Exact. Results: Perceived stigma was related to the use of CST services among PLHIV. The perception of stigma that is most often felt by PLHIV is the perception of stigma about PLHIV themselves (self-stigma), where PLHIV feel afraid that other people will not accept them if they know their status. PLHIV also feel that they are not well because there is HIV in their body. If self-stigma is not handled, it will affect the quality of life of PLHIV. Conclusion: One way to reduce self-stigma is for PLHIV to regularly participate in Peer Support Groups. At the Peer Support Group, massive discussions can also be held regarding efforts to improve the quality of life of PLHIV. Pendahuluan: Layanan perawatan, dukungan, dan pengobatan (CST) merupakan salah satu layanan yang dibutuhkan oleh ODHA. Layanan ini dapat meningkatkan kualitas hidup ODHA, namun masih terdapat ODHA yang tidak memanfaatkan layanan tersebut secara rutin. Tujuan penelitian ini adalah menganalisis hubungan antara stigma yang dirasakan dengan pemanfaatan layanan CST. Metode: Jenis penelitian ini adalah kuantitatif yaitu analitik observasional (cross sectional). Penelitian ini dilakukan di Kelompok Dukungan Sebaya Solo Plus Surakarta dengan jumlah sampel 110 ODHA yang diambil dengan menggunakan teknik exhaustive sampling. Variabel bebas adalah stigma yang dirasakan dan variabel terikat adalah pemanfaatan layanan CST. Instrumen pengukuran persepsi stigma menggunakan Berger HIV Stigma Scale sedangkan pemanfaatan layanan CST diukur menggunakan kuesioner yang melihat perilaku dalam enam bulan terakhir. Analisis data dilakukan dengan menggunakan Fisher Exact. Hasil: Stigma yang dirasakan berhubungan dengan pemanfaatan layanan CST pada ODHA. Persepsi stigma yang paling sering dirasakan oleh ODHA adalah persepsi stigma terhadap ODHA itu sendiri (self-stigma), dimana ODHA merasa takut orang lain tidak akan menerima mereka jika mengetahui status mereka. ODHA juga merasa dirinya tidak sehat karena terdapat HIV di dalam tubuhnya. Apabila self-stigma tidak ditangani, maka akan mempengaruhi kualitas hidup ODHA. Kesimpulan: Salah satu cara untuk mengurangi self-stigma adalah ODHA secara rutin mengikuti Kelompok Dukungan Sebaya. Di Kelompok Dukungan Sebaya juga dapat dilakukan diskusi secara masif terkait upaya peningkatan kualitas hidup ODHA.